PHYSICAL EXERCISES, GAMES AND SPORT CONTESTS ON THE TERRITORY OF DACIAN PROVINCES - Horea MOȘNEAG; Codruța Florina BULDUȘ (Studia Universitatis Babeş-Bolyai: Educatio Artis Gymnasticae, 2015)
The aim of this paper is to bring the history of sport and physical education in the province of Dacia in the current knowledge on the subject of the Roman Empire, respectively from more developed provinces of the Empire. The work completes the basic dates regarding the integration of the Province of Dacia in the Empire structures and assuming the Roman models, contributing in this way to complete the idea of the romanization of the province. The number of evidence about "sports branch" is smaller, and its representation is modest compared with those of the oldest and most developed provinces than Dacia and, in fact, better and more researched, but more important to us it the fact that it can be shown that it exist a part of every branch of sport life. The fact that certain representations and local daco-roman artifacts produced present a great resemble to products from other provinces (eg. representation on bricks of gladiators) shows that there were general knowledge about these games that crossed border.